1980
DOI: 10.1037/0021-843x.89.1.101
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive theory and the generality of pessimism among depressed persons.

Abstract: 38 depressed (as measured by the Beck Depression Inventory) and 52 nondepressed college students were given a series of anagrams to solve. A 1-chance subgroup was informed that they would win a free movie ticket if they were successful in the task. A 2nd-chance subgroup received the same instructions as the 1-chance subgroup but were also informed that if they failed, they would have another opportunity in a different, undefined task. Ss were subdivided into success and failure subgroups that either succeeded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…It should be noted that the present research did not study nonnormal, nondepressed subjects; hence the finding that some attributions may be causes of depressive symptoms does not preclude the possibility that such attributions may also mediate symptoms of other disorders. Further, as has often been noted about studies of depression in college student populations (e.g., Golin, Jarrett, Stewart, & Drayton, 1980), although they are of interest in their own right, it does not necessarily follow that the present findings are generalizable to clinically depressed groups (see Golin & Hartz, 1979); the extent to which the present results are applicable to a clinical group can only be determined by further study.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…It should be noted that the present research did not study nonnormal, nondepressed subjects; hence the finding that some attributions may be causes of depressive symptoms does not preclude the possibility that such attributions may also mediate symptoms of other disorders. Further, as has often been noted about studies of depression in college student populations (e.g., Golin, Jarrett, Stewart, & Drayton, 1980), although they are of interest in their own right, it does not necessarily follow that the present findings are generalizable to clinically depressed groups (see Golin & Hartz, 1979); the extent to which the present results are applicable to a clinical group can only be determined by further study.…”
Section: Discussionmentioning
confidence: 57%
“…Beck, 1976). Golin, Jarrett, Stewart, and Drayton (1980), however, found that informing depression-prone persons of a possible second chance to attain a goal serves to reduce stress experienced during their first attempt at goal attainment. These findings suggest an apparent paradox; depression-prone persons appear to be pessimistic about their prospects for future success and yet are ostensibly less stressed when they have more than one opportunity to attain a goal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, these effects persisted 24 h after completion of the tasks. Finally, Golin, Jarrett, Stewart, and Drayton (1980) used an anagram task and demonstrated a main effect of a success-failure manipulation on depression scores on the Multiple Affect Adjective Check List.…”
Section: Effects Of Task Outcome and Subjective Standard On State Depmentioning
confidence: 99%
“…Because of its ease of administration and principal focus on subjective feelings, it has also been used to assess the presence and intensity of depressive features in nonclinical populations sampled for various purposes (Barker & Jessup, 1980;Bosse, Croghan, Greenstein, Katz, Oliver, Poweli, & Smith, 1975;Bumberry, Oliver, & McClure, 1978;Golin & Hartz, 1979;Golin, Jarrett, Stewart, & Drayton, 1980;Hammen, 1980;Hammen & Padesky, 1977;LaPointe & Crandell, 1980;Miller & Seligman, 1975;Oliver & Burkham, 1979;Olive r & McGee, 1982;Propst, 1980). As a result, more is known about the psychometric properties of the BDI when used with college students.…”
mentioning
confidence: 97%